Dr. Mercedes Verónica Diego Cobelo in the history of Cienfuegos’ Stomatology - Perla Margarita Pacheco Morffi; Ana Belkys Hernández Millán; José Danilo Pacheco González; Enedys Chacón Najarro; Félix Alberto Companioni Landín (Medisur)
There are many women who have contributed to the development of Stomatology in Cuba. In Cienfuegos, one of the most prominent in this field is Dr. Mercedes Verónica Diego Cobelo, a personality that this article intends to address through the description of the significant events of her life and work, going through her career in the student, labor and political fields. A historical research was carried out, from October to December 2016. As a way of reviewing the history, her memories were used; as well as the analytic-synthetic and deductive-inductive methods. Historical research techniques were used: documentary review; and in-depth oral interviews with testimony from Mercedes herself, as the primary source for obtaining the information. She is considered the initiator of stomatology and medical education in Cienfuegos province since 1970, by participating in the inauguration of the stomatology services of all its municipalities, in addition to being elected provincial president of the Cuban Society of Public Health. The study evidences the transcendence of her work in the establishment of stomatological services in Cienfuegos, her dedication to teaching from her student stage, and the integral link to the revolutionary work in all areas.